Structural Studies on Fe60Cu40 System Bimetals of Mechanical Alloying - 刘方新 韦世强 高琛 刘文汉 杨元政 董远达 (中国科学通报：英文版, 1994)
Mechanical alloying (MA), which has been described by Benjamin, is an industrialpowder metallurgy method known from the 1970s. In recent years, MA producesmany new materials. Especially it can be used to synthesize amorphous alloy whichcannot be alloyed ordinarily by rapid liquid quenching (including metals which areimmiscible in liquid state, or in composition region near non-cocrystalline point), sothis method has been studied intensively in preparing amorphous alloys. Anotheruse of the method is to extend the solid state solution of certain immiscible metals.